USE HIGH RESOLUTION SHALLOW SEISMIC PROFILES AND SEDIMENT CORER IN THE STUDY THE SHORELINE, ERODED SURFACE OF OLD FORMATIONS AND OLD RIVERS ON THE SOUTHERN CENTRAL SHELF IN LATE PLEISTOCENE- HOLOCENE - Hai, Nguyen Tien; Schimanski, A. (Vietnam Journal of Marine Science and Technology, 2007)
On the basis of the data interpretation from high resolution shallow seismic profiles (Boomer) and sediment corer has helped to establish a schema of the shorelines, eroded surface of old formations and old rivers on the Southern Central shelf in the end of Late Pleistocene - Holocene. Coastal zone of -90 – -130 m, the shoreline was located at rite depth of -109 – -20 m, about 14700 - 10000 years BP: Coaslal zone of -50 – -70 m, the shoreline was located at the depth of -60 m, about 10000 years BP: Coastal zone of -20 – -40 m, the shoreline was located at the depth of -30 m (about 9200 - 8500 years BP): Coastal zone of -10 – 10 m, the shoreline was located at the depth of 5 m (about 5000 - 4000 years BP), -1.5 m (about 2500 years BPJ and 2.5 m (about 2000 years BP). The eroded surface of old formations and paleocoastline in Nha Trang shelf were developed in a narrow zone due to step slope while that off Vung Tau – Binh Thuan shelf formed in a wide: one due to gentle hill slope. The old Mekong - Dong Nai rivers were developed in Vung Tau – Binnh Thuan shelf during times of Sea level lowstand in the end of Late Pleistocene - Early Holocene.